Cover Image, Volume 3, Number 2, June 2021. Issue 2 (15th June 2021) - Zhang, Chong; Shin, Woochul; Zhu, Liangdong; Chen, Cheng; Neuefeind, Joerg C.; Xu, Yunkai; Allec, Sarah I.; Liu, Cong; Wei, Zhixuan; Daniyar, Aigerim; Jiang, Jia‐Xing; Fang, Chong; et al.
Abstract : Front cover image : Despite the remarkable progress made on high‐performing cathode materials, the showstoppers of aqueous Zn‐metal batteries are the dendrite problem and poor reversibility of zinc‐metal anode (ZMA). In article number 10.1002/cey2.70, research teams by Xiulei Ji, Jia‐Xing Jiang, Chong Fang and P. Alex Greaney collaborated to develop a ZnCl2/LiCl mixture water‐in‐salt electrolyte, in which the high concentration makes the water molecules robust and the additive of Li+ leads to an electrostatic shield eff ect to restrict the growth of Zn dendrites. As a result, the ZMA shows a high Coulombic effi ciency and dendrite‐free morphology.